Da’wah approach to the strawberry generation: A study on Yuk Ngaji TV channel - Rohman, Angga Nur; Nurdin, Ali; Eken, Metin; Bax, Wazir Baksh (Islamic Communication Journal, 2023)
The strawberry generation, Generation Z, has much potential but a fragile mentality like a strawberry, even though Indonesia will get a demographic bonus at a productive age. This is the responsibility of da'wah because it is part of the object of da'wah. YukNgaji TV is a channel that seeks to overcome the problems of millennial teenagers. The research aims to examine the da'wah approach of the YukNgaji TV channel for the strawberry generation using a content analysis approach, where data is collected using documentation and observation techniques. The findings were that the preacher of the channel was chosen from Generation Z (still young), an influencer with advanced knowledge. The da’wah method uses casual sharing discussions, lectures, inspirational stories, and brainstorming. The YouTube media is packaged with live streaming and live events and posting da'wah content, which contains themes of youth, morals, and relationships for the strawberry generation. The effects on the strawberry generation can be cognitive and affective, but further investigation is needed regarding the behavioral effects of the strawberry generation. In this way, the study can contribute to developing preaching approaches that are always required to be dynamic. ***Generasi strawberi merupakan generasi Z yang memiliki banyak potensi, namun memiliki mental rapuh seperti layaknya buah strawberi, padahal Indonesia akan mendapatkan bonus demografi di usia yang produktif. Hal tersebut menjadi tanggungjawab dakwah, karena menjadi bagian dari objek dakwah. YukNgaji TV menjadi channel yang berupaya untuk mengatasi permasalahan remaja milenial ini. Tujuan penelitian untuk mengkaji pendekatan dakwah channel YukNgaji TV bagi generasi strawberi dengan menggunakan pendekatan content analysis, dimana data dikumpulkan dengan teknik dokumentasi dan observasi. Temuannya adalah bahwa pada penelitian channel dakwah ini, berbagai pendekatan dakwah digunakan untuk menjawab persoalan dari generasi strawberi. Pendakwah dipilih dari generasi Z (masih muda), seorang influencer yang memiliki keilmuan yang mumpuni. Metode dakwah dilakukan dengan diskusi sharing santai, ceramah, cerita inspiratif dan brainstorming yang jarang dipakai didunia dakwah. Media pengantar pesan dakwah melalui youtube yang dikemas dengan live streaming dan live event serta postingan konten dakwah, yang berisikan tema keremajaan dan akhlak serta pergaulan bagi generasi strawberi. Efek bagi generasi strawberi ini dapat berupa kognitif dan afektif, namun perlu pendalaman terkait efek behavioral bagi generasi strwaberi. Dengan demikian studi dapat berkontribusi bagi pengembangan pendakatan dakwah yang dituntut untuk selalu dinamis.